Predisclosure Information Search Incentives, Analyst Following, and Earnings Announcement Price Response. - Dempsey, Stephen J. (The Accounting Review, 1989)
ABSTRACT: This paper Investigates an exogenous proxy for predisclosure information, analyst following, and empirically contrasts its earnings announcement price response performance with the endogenous firm size factor. The theoretical motivation for the comparison rests on the premise that the analyst community formulates its preference ranking of firms to follow on the basis of a multivariate information search cost-benefit framework (i.e., incentive considerations in addition to size). The empirical results, based on 2,466 annual earnings announcements over 1976-1982, are consistent with this hypothesis. Regression analyses corroborate the firm size effect found in prior studies as well as a univariate analyst following effect. In a multiple regression model, however, analyst following continues to be incrementally significant while firm size does not. Further analysis demonstrates that thinly followed large firms have significantly larger price reaction than widely followed small firms. Both are supportive of a "non-size-related" analyst following effect.